Is English Teachers Forum Contributive to Teachers’ Professionalism Development? Voices from Indonesian EFL Teachers - Susanto Susanto (Script Journal: Journal of Linguistics and English Teaching, 2022)
In Indonesian context, teachers’ competencies in terms of set of knowledge, skills, and behaviors are explicitly stated in the Indonesian Law No. 14/2005 on Lecturers and Teachers. Some previous studies dealing with teachers’ professional development have been conducted by some researchers. They have focused on investigating teachers’ efforts to improve their professional competence in the domain of academic qualification. Some studies also have focused on identifying effective teachers. However, little studies have scrutinized how the teachers’ professional development is improved through Teachers Forum. This present study investigated English teachers’ viewpoints on their involvement in the Teacher Forum and how it was contributive on their professional development in carrying out their professional tasks. This Ethnographic- Qualitative study involved the chief and four members of Teachers Forum. The data were collected through interview and they were analyzed applying the procedures suggested by Spradley (1979) covering domain analysis, taxonomic analysis, componential analysis, and theme analysis. The findings revealed that the participants had a good perception on the Teachers Forum for it was potential for them to develop their pedagogical competence. The contributions supporting the pedagogical competence from routine involvement and development programs of the Teachers Forum were 1) understanding and caring of the students’ uniqueness, conducting teaching and learning activities (setting instructional objectives, doing teaching activities, assessing students’ performance), 2) selecting ICT-based teaching media, conducting researches, doing self-teaching reflection, and 3) guiding the students to improve their English performance